Efeito da suplementação de metionina sobre o desempenho e a avaliação de carcaças de frangos de corte - Whitaker, H. M.A. [UNESP]; Mendes, A. A. [UNESP]; Garcia, E. A. [UNESP]; Roça, R. O. [UNESP]; Varolli, J. C. [UNESP]; Saldanha, E. P.B. [UNESP] (My University, 2002)
One experiment was conducted to evaluate the effect of dietary additional methionine levels during the grower period (22 a 42 days of age) on performance, carcass yield, and chemical composition of broiler chickens. Two thousand sexed Ross broilers, were reared in a randomized factorial 2×5 design (sex and methionine levels) with four replications of 50 birds each. Experimental diets were formulated to contain 100%, 110%, 120%, 130% and 140% of methinine level suggested by NRC (1994). Methionine levels were, .38, .42, .46. .50 and .54%, respectively. At 42 days of age birds were slaughtered to evaluate carcass yield, abdominal fat and chemical composition. Increasing methionine level did not affect (p>.05) weight gain, feed consumption, feed conversion, mortality, abdominal fat, and carcass yield and breast and thigh moisture, protein, fat and ash.. Interaction between methionine level and sex was not significant (p>.05), but females presented higher abdominal fat (p<.05) than males. As methionine level did not affected performance and carcass yield and composition, it was concluded that the methionine level during grower period (22 to 42 days of age) suggested by NRC (1994) is adequate.
Effect of methionine supplementation on performance and carcass yield of broiler chickens
Keywords: Broiler chickens; Carcass yield; Chemical composition; Methionine